A mobile app as support for pelvic floor muscle training started prior to radical prostatectomy. Issue 1 (9th March 2022) - Al‐Zaidi, Zinah; Lindam, Anna; Fransson, Per; Samuelsson, Eva
Abstract: Objective: To evaluate the usefulness of a mobile app to support pelvic floor muscle training (PFMT) started prior to radical prostatectomy (RP). Materials and methods: A prospective cohort study conducted in Sweden from June 2018 to February 2021 including men for whom RP was planned within 12 months. Users responded anonymously to questionnaires at baseline, 1 and 3 months. Our primary aim was to evaluate if the app could facilitate PFMT and increase confidence in performing pelvic floor muscle (PFM) contractions correctly. Our second aim was to describe the change in urinary incontinence (UI) after RP, based on the International Consultation on Incontinence Questionnaire‐Urinary Incontinence Short Form (ICIQ‐UI SF). Results: Of the 3043 users at baseline, 388 met the primary inclusion criteria. Of those, 71 (18.3%) were incontinent, predominantly with slight symptoms. The most common type was urge UI, 39/71 (54.9%). Of the 388 users, 159 (41.0%) answered the questionnaire at 1 month, and 131 (33.7%) at 3 months within 89–135 days. Of those 131, 127 (96.9%) indicated that the app facilitated their training 'a lot' or 'somewhat'. Confidence in performing PFM contractions correctly increased from 39.7% at baseline to 74.0% at 1 month and 87.8% at 3 months ( p < 0.001). At baseline, 19.8% performed PFM contractions at least daily, which increased to 74.0% at 1 month and 77.9% at 3 months ( p < 0.001). At 3 months, 115/131 (87.8%) had undergone RP, 93.6% of which were robot‐assisted. Of the 115, 103 (89.6%) were incontinent, and stress UI dominated. The mean ICIQ‐UI SF score increased from 1.2 (2.4 SD) at baseline to 9.6 (5.2 SD), p < 0.001, after surgery. Conclusions: The mobile app facilitated pelvic floor muscle training for men who were planned to undergo radical prostatectomy and used the app.